{21-[17-(2x+1):3]:2+6}×2-17=23
Răspunsuri la întrebare
Răspuns de
5
{21-[17-(2x+1):3]:2+6}×2-17=23
{21-[17-(2x+1):3]:2+6}×2=23+17
{21-[17-(2x+1):3]:2+6}×2=40
21-[17-(2x+1):3]:2+6=40:2
21-[17-(2x+1):3]:2+6=20
21-[17-(2x+1):3]:2=20-6
21-[17-(2x+1):3]:2=14
[17-(2x+1):3]:2=21-14
[17-(2x+1):3]:2=7
17-(2x+1):3=7×2
17-(2x+1):3=14
(2x+1):3=17-14
(2x+1):3=3
2x+1=3×3
2x+1=9
2x=9-1
2x=8
x=8:2
x=4
{21-[17-(2x+1):3]:2+6}×2=23+17
{21-[17-(2x+1):3]:2+6}×2=40
21-[17-(2x+1):3]:2+6=40:2
21-[17-(2x+1):3]:2+6=20
21-[17-(2x+1):3]:2=20-6
21-[17-(2x+1):3]:2=14
[17-(2x+1):3]:2=21-14
[17-(2x+1):3]:2=7
17-(2x+1):3=7×2
17-(2x+1):3=14
(2x+1):3=17-14
(2x+1):3=3
2x+1=3×3
2x+1=9
2x=9-1
2x=8
x=8:2
x=4
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă